Treatment of subtrochanteric fracture femur by open reduction and internal fixation by long proximal femoral nailing - Munavalli, Prabhu P.; G., Gururaj N. (International Journal of Research in Orthopaedics, 2019)
Background: Subtrochanteric fractures are devasting injuries that most commonly affect the elderly population and also in young. Methods: This is a prospective study of 20 cases of subtrochanteric fracture admitted to KIMS, Huballi between November 2008 to August 2010 treated with left proximal femoral nail (LPFN) by open method. Cases were taken according to inclusion and exclusion criteria, i.e., fresh subtrochanteric fracture in adults. Pathologic fractures, multiple fractures, fractures in children, old neglected fractures were excluded from the study. Objectives of this study were to study subtrochanteric fractures and to determine effectiveness of LPFN in tretment of subtrochanteric fractures by open reduction and internal fixation (ORIF). Results: In our study of 20 cases, there were 16 male and 4 female patients with age ranging from 17 years to 75 years with most patients in between 21-40 years. 65% of the cases admitted were road traffic accidents, 25% due to fall from height and 10% due to trivial fall with right side being more common side affected. Russell and Taylor type IA fracture accounted for 40% of cases. Mean duration of hospital stay was 24 days and mean time of full weight bearing was 14 weeks in our patients. Good to excellent results were seen in 85% of cases in our study. Conclusions: Subtrochanteric fractures of femur can be successfully treated by ORIF by LPFN resulting in proper anatomical reduction and hence alignment and high rate of bone union.